Modeling and control of snake robots - Nguyen, Văn Phước (Journal of Technical Education Science, 2014)
Currently, modeling and simulation of Snake robots become necessary to correct decision prior to the actual application. This paper presents the construction of the modeling describing the movement structure and the control method of the Snake robots. The PID controllers are used as robot controllers. Results of the Snake robot simulation including sixlinks are performed on Matlab/Simulink which is proved that the direction signal, velocity and angle phi of the output signals response to the input signals.